(3QSGdI aj JYQja GdadSaIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3GdaGQGHi GdMceI ai eHGOF GdQCi hai GdMbjbI gi Gf jMUd GdGfSGf GdYdhe GdfXQjI hGf jchf GaYGdg cdgG ehGabg deG gh Lejd s
(3BNQgG (B:s
(3Gf jZGdWg HgG YfO eNGWHJg EjGg hGdhLg GdPi Hg jJMQR ajeG Hjfg hHjf faSg ef GdeZGdWGJ hgh faS GdhLg GdPi jOaY Hg Yf faSg eG jZGdWg ZjQg JeJ hddg GdMeO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs